Genetic investigations of autosomal recessive inherited ichthyosis impressed by fetal ultrasound: Exome sequencing and haplotype linkage analysis - Ting-Yu Chang; Zhu Wei Lim; Yi-Tzu Chu; Wan-Ju Wu; Mei-Hui Lee; Shun-Ping Chang; Dong-Jay Lee; Wen-Hsiang Lin; Ming Ho; Jin-Chung Shih; Gwo-Chin Ma; Ming Chen (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Ichthyosis are complex skin diseases, characterized by hyperkeratosis with various degrees of thickening, desquamation, and erythema. The prenatal diagnosis of ichthyosis is challenged due to the clinical and genetic heterogeneity and the late-onset of fetal features on ultrasound scan. Here, we reported two fetuses with Harlequin ichthyosis (HI), a severe subtype of autosomal recessive congenital ichthyosis (ARCI), who were diagnosed prenatally by images and genetic investigations. Preimplantation genetic testing (PGT) was also performed in one case and the family to prevent the transmission of this condition. Materials and methods: Fetal images were analyzed by detailed fetal ultrasound. Genetic defects in affected fetuses were detected using whole exome sequencing (WES) and confirmed by Sanger sequencing. PGT for monogenic disease (PGT-M) was performed using short tandem repeat (STR) markers and amplification refractory mutation system quantitative polymerase chain reaction (ARMS-qPCR). Results: WES identified pathogenic mutations in ABCA12 gene in both fetuses. Genome Analysis ToolKit (GATK 4 version 4.2.1.0) was merged using a setting of the trio model for exome variation analysis. Confirmatory Sanger sequencing of ABCA12 gene was also applied to both parents. Disease-cause haplotyping by STR markers and ARMS-qPCR for PGT-M strategy were conducted in family 1. Linkage analysis in conjunction with STR was used in the first case, whereas unequal coverage of WES was deciphered with the inspiration of the second case a few years later. Both cases were diagnosed by high coverage WES and led to successful subsequent pregnancies by preimplantation genetic diagnosis and genetic amniocentesis. Conclusion: Preimplantation genetic testing using STR linkage analysis can rescue cases with autosomal recessive inheritance when only one mutation is found in the putative gene, while reanalysis of high-coverage WES by optimized updated bioinformatics should always be considered in addition to whole genome sequencing.